Relative bee abundance varies by collection method and flowering richness: Implications for understanding patterns in bee community data. Issue 2 (31st May 2021) - Kuhlman, Marirose P.; Burrows, Skyler; Mummey, Daniel L.; Ramsey, Philip W.; Hahn, Philip G.
Abstract: Recent declines in wild bee populations have led to increases in conservation actions and monitoring of bee communities. Pan traps are a commonly used sampling method for monitoring bee populations due to their efficiency and low cost. However, potential biases inherent in different sampling techniques may result in misleading characterizations of bee communities across space and time. In this paper, we examined how bee communities sampled using pan traps and aerial nets changed seasonally, and if they were affected by the availability of floral resources. We found strong seasonal changes in the abundance, but not the richness, of bees captured in pan traps. Notably, we captured the fewest bees during weeks in spring when most flowering plant species were in bloom, suggesting that floral resource availability influences pan trap captures. We also compared patterns of bee abundance in pan traps to those captured by aerial netting. Bee richness in pans and nets was positively correlated, but relative abundances in pan and net samples were dominated by different bee genera. Furthermore, most genera decreased in pans with increasing floral richness, but patterns were mixed for nets. When using presence/absence data, rather than abundance, community composition was more similar between netted and pan‐trapped bee communities and changed less substantially across the floral richness gradient. Overall, these differences led to sampling substantially different bee community compositions in pan traps versus nets, especially when using abundance‐based methods to characterize the bee community. By examining multiple years of intensive seasonal sampling of plant and bee communities, we document potential pitfalls with methods commonly used to sample bee communities. We suggest that pan trapping and aerial netting provide similar estimates of bee species richness and community composition when using presence/absence data, but that practitioners should interpret pan‐trapped bee abundance data with caution especially when comparing bee communities between sites where plant communities may differ. Abstract : We found that relative abundances of bees differed with capture method, and that some bee genera responded strongly to either pans traps or nets. We also found a strong overall inverse relationship between bee abundance in pan traps and flowering richness in early season, suggesting that floral richness can influence the traps' reliability in predicting true bee abundance. However, bee community composition, measured as the relative presence/absence among genera, was more consistent both between nets and pans as well as across a floral richness gradient.